Implementasi Model Blended Project Based Learning Untuk Meningkatkan Keterampilan Literasi Digital Mahasiswa Calon Guru SD - Wijayanti, Arfilia; Fajriyah , Khusnul; Suyitno (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2022)
This study aims to determine the increase in digital literacy and the response of prospective elementary school teacher students to the implementation of the Blended Project Based Learning model. This research is a quasi-experimental research (pre-experiment) with a one group shoot case study design. This study consisted of one experimental class that received a treatment, which was given learning with the Blended Project Based Learning model to improve digital literacy, then at the end of the lesson its effectiveness was analyzed by analyzing the increase (N-Gain) of digital literacy, as well as the responses of prospective elementary school teacher students at the University of PGRI Semarang towards the ongoing learning process. It is concluded that the implementation of the Blended Project Based Learning model can improve students' digital literacy at high criteria. Students also responded that the implementation of the Blended Project Based Learning model had been going very well during the learning process. Keywords: Blended Project Based Learning, digital literacy, elementary school teacher candidates, science learning.